ORGANIZING THE IMPLEMENTATION OF CURRICULUM OF DIKLATPIM IV IN THE HUMAN RESOURCES DEVELOPMENT AGENCY NORTH SUMATRA PROVINCE - Suriya Jaya (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This study aims to find the organization of the implementation of the level IV education and leadership training curriculum (Diklatpim IV) in the Human Resources Development Agency (BPSDM) of North Sumatra Province (North Sumatra Province ). The research focus is, "Organizing the Implementation of the IV Education and Training Curriculum in BPSDM North Sumatra Province ", using naturalistic qualitative methods. Data collection techniques used interviews, observation, document study, data analysis using the interactive model of Miles and Huberman, checking the validity of the data based on Lincoln and Guba. This study found: First, the function of organizing curriculum implementation is carried out at the institutional and class stages. Second, organizing the implementation of the institutional stage curriculum is carried out by dividing the roles and duties of structural officials and staff in management, correspondence administration, and finance tasks, these tasks are interrelated. Third, some of the lecturers were assigned not based on the competency of the Training of Facilitator (TOF) as outlined in the planning stage of the institution. Fourth, at the class stage of organizing the curriculum implementation by widyaisawara on the learning stages, methods, learning resources, and learning media. Keywords: Organizing, Curriculum Implementation, Education and Training